Real-scale investigation of liquid CO2 discharge from the emergency release coupler of a marine loading arm - Al Baroudi, Hisham; Wada, Ryota; Ozaki, Masahiko; Patchigolla, Kumar; Iwatomi, Makoto; Murayama, Kengi; Otaki, Toru (Elsevier, 2022)
Carbon capture, utilisation and storage has been recognised as a necessary measure to reduce greenhouse gas emissions. CO2 shipping represents a promising transportation option that offers flexible sink-source matching to enable decarbonisation at a global scale. In order to implement safe and reliable loading and offloading operations at the terminal, marine loading arms require the integration of emergency release systems in the event of sudden movement of the ship away from the berthing line. In this study, a cryogenic test facility was constructed to handle CO2 in proximity of the triple point (∼0.9 MPa[abs] – 1.7 MPa[abs], 227 K - 239 K) and replicate the principles of an emergency release coupler during a shutdown, with the aim of investigating the CO2 discharge and dispersion behaviour, and determining the implications on coupler design and safety protocols. Findings show that separation of the test vessel leads to an abrupt discharge of the liquefied CO2 inventory and several phase transitions within 0.6 s of the start of the discharge in all tests. The clouds disperse in a ‘tulip’ shape that could be clearly observed from afar, and generation of carbon dioxide solids was observed on the vessel surface in all performed tests, bringing the temperature inside the vessel to approximately 190 K. The implementation of protective barriers is expected to reduce the impact of the release, though the risk of asphyxiation or cryogenic burns to surrounding personnel cannot be ruled out given the magnitude of the discharge process.
Keywords: GHG; Carbon capture; utilisation and storage; CO2 transport; CO2 shipping; Marine loading arm; Emergency release system